2006
DOI: 10.1021/ol061024z
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Synthesis of Thapsigargin:  Enantioselective Synthesis of 7,11-Dihydroxyguaianolides

Abstract: [reaction: see text] The enantioselective synthesis of a 7,11-dihydroxyguaianolide bearing the stereochemistry present in thapsigargin, a potent and selective inhibitor of the Ca(2+) SERCA-ATPase pumps, is described. Starting from (+)-dihydrocarvone, the synthesis presents two key steps. The first one involves the photochemical rearrangement of a gamma,delta-unsaturated ketone eudesmane into the corresponding guaiane. The second step consists of the regioselective oxidation of an unprotected tetrahydroxylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…388 An enantioselective synthesis of a 7,11-dihydroxyguaianolide, possessing the stereochemistry of thapsigargin, has been described. 389 A study of a thapsigargin derivative has revealed the importance of the length and flexibility of the side chain attached to O-8 in the activity of this sesquiterpene lactone, and its analogues, towards prostate cancer cells. 390 Five novel pseudoguaianolides, dichrocepholides A-E 460-464, have been isolated from Dichrocephala integrifolia.…”
Section: This Journal Is © the Royal Society Of Chemistry 2007mentioning
confidence: 99%
“…388 An enantioselective synthesis of a 7,11-dihydroxyguaianolide, possessing the stereochemistry of thapsigargin, has been described. 389 A study of a thapsigargin derivative has revealed the importance of the length and flexibility of the side chain attached to O-8 in the activity of this sesquiterpene lactone, and its analogues, towards prostate cancer cells. 390 Five novel pseudoguaianolides, dichrocepholides A-E 460-464, have been isolated from Dichrocephala integrifolia.…”
Section: This Journal Is © the Royal Society Of Chemistry 2007mentioning
confidence: 99%
“…12 On the other hand, guaiane 25 is an intermediate that can be prepared by following a methodology that we devised for the synthesis of analogues of thapsigargin. 13 To this end, compound 23 was subjected to photochemical rearrangement in AcOH, providing 24 in 72% yield. Subsequent protection of the primary hydroxyl group with TBDMSCl and imidazole afforded guaiane 25 in almost quantitative yield (Scheme 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8,7.8,5.2,2.6 Hz,1H), 2.09 (dddd, J = 17. 1, 12.7, 12.7, 5.2 Hz, 1H), 1.97 (s, 3H), 1.70 (tq,J = 7.4,7.4 Hz,2H), 0.97 (t, J = 7.4 Hz, 3H); 13 C NMR (126 MHz,CDCl 3 ) δ 193.7,173.0,162.3,125.6,72.9,36.2,30.6,28.4,24.3,18.6,13.7; IR (film) ν max 2966,2936,2876,1743,1689,1633,1381,1177,1104 7, 173.2, 162.3, 125.6, 72.9, 34.3, 31.4, 30.5, 28.4, 24.7, 24.2, 22.4, 14.0; IR (film) ν max 2956,2933,2872,1743,1690,1633,1380,1208,1167,1103 3-Methyl-6-octanoyloxycyclohex-2-enone (11). Yellow oil (47 mg, 74%); 1 H NMR (400 MHz, CDCl 3 ) δ 5.90 (br s, 1H), 5.31 (dd, J = 13.3, 5.4 Hz, 1H), 2.55 (m, 1H), 2.39 (m, 3H), 2.22 (dddd, J = 7.…”
Section: Scheme 2 Synthesis Of Compound 36 From 33mentioning
confidence: 99%
See 1 more Smart Citation
“…[52] A high-yielding dehydration of 134 afforded the fully conjugated system 135, which underwent a remarkably chemoselective asymmetric dihydroxylation of the side chain to furnish diol 136. Upon irradiation in acetic acid, hydroazulene core 137 was formed.…”
Section: Hemi-synthesis Starting From Santoninmentioning
confidence: 99%